A critical review of polycyclic aromatic hydrocarbon phototoxicity models. (2nd February 2017) - Marzooghi, Solmaz; Di Toro, Dominic M.
Abstract: Polycyclic aromatic hydrocarbons (PAHs) are known to exhibit photo‐induced toxicity. Hundreds to thousands of PAH parent and substituted compounds are found in the environment, and developing a predictive model applicable to a wide variety of PAHs and organisms is a necessary precursor to environmental risk assessments. There has been evolutionary progress in phototoxicity modeling since 1977. In the present study, a comprehensive review of the models developed to predict phototoxicity of PAHs is presented. The contributions of each of the models to the state of the art are discussed. The models are compared in terms of their scope of applicability to different organisms, PAHs, endpoints (median lethal time and median lethal concentration), and light conditions. The current state of the science that accounts for the key elements of phototoxicity modeling, including the differences in species sensitivity, the partitioning of PAHs into the target lipid of the organisms, and light absorption by the chemicals, as well as light exposure time and conditions, is discussed. In addition, the remaining issues that need to be addressed are explored: the effect of time‐varying exposures to light and PAH concentrations, and the lack of a mechanistic understanding that can explain the failure of the Bunsen–Roscoe law of reciprocity. Environ Toxicol Chem 2017;36:1138–1148. © 2016 SETAC